2016
DOI: 10.1097/jcp.0000000000000493
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind, Randomized, Placebo-Controlled Trial of Metoclopramide for Hypersalivation Associated With Clozapine

Abstract: Hypersalivation is a frequent, disturbing, and uncomfortable adverse effect of clozapine therapy that frequently leads to noncompliance. The aim of this study was to examine the efficacy of metoclopramide (dopamine D2 antagonist, antiemetic medication) as an option for management of hypersalivation associated with clozapine (HAC). A 3-week, double-blind, placebo-controlled trial was conducted in university-based research clinics from January 2012 to May 2014, on 58 inpatients treated with clozapine who were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…The mechanism of metoclopramide in reducing hypersalivation is not clearly defined. Substituted benzamide derivatives do not have adrenergic antagonistic, anticholinergic, or adrenomimetic properties [ 4 ]. Previous trials with this group of drugs with high selective binding to the dopamine D 2 /D 3 receptors have shown efficacy in treating CIH [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of metoclopramide in reducing hypersalivation is not clearly defined. Substituted benzamide derivatives do not have adrenergic antagonistic, anticholinergic, or adrenomimetic properties [ 4 ]. Previous trials with this group of drugs with high selective binding to the dopamine D 2 /D 3 receptors have shown efficacy in treating CIH [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, metoclopramide stimulates gastric motility and exerts its prokinetic effect by antagonising dopamine mediated relaxation effect on gastrointestinal smooth muscle [ 3 ]. Besides the anti-emetic and prokinetic effects of metoclopramide, it is believed that the peripheral activity of the drug can reduce secretion of saliva, and hence it has been considered as a treatment option for clozapine-induced hypersalivation (CIH) also known as sialorrhea [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Botulinum toxin, metoclopramide, and tricyclic antidepressants are additional agents that have varying degrees of evidence for the management of clozapine-induced sialorrhea. [10][11][12] a 2A Adrenergic receptor agonists, such as clonidine, have also been reported in case reports 2,13,14 to be effective at managing clozapine-induced sialorrhea. Clonidine is generally well tolerated, but it is imperative that clinicians monitor a patient's blood pressure if clonidine is used concomitantly with clozapine.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment options suggested in CIS are glycopyrrolate, biperiden [5], amisulpride augmentation [6], scopolamine (hyoscine) butylbromide [7], and low-dose amitriptyline [8]. In a recent study, metoclopramide was found effective and safe in CIS [9]. All systemic agents that are used for sialorrhea may increase clozapine's side effects such as blood pressure changes, constipation, and arrhythmias or may have a negative impact on cognition [5].…”
Section: Introductionmentioning
confidence: 99%